The pattern of tooth loss due to dental caries and periodontal disease among patients attending dental department (OPD), Dhulikhel Hospital, Kathmandu University Teaching Hospital (KUTH), Nepal - Upadhyaya, C; Humagain, M (Kathmandu University Medical Journal, 2009)
Aims and objectives: The aim of this study was to investigate the type of tooth usually associated with extraction due to caries or periodontal disease and its relation to age at which these were lost, among patients attending dental surgery outpatient clinic, Dhulikhel Hospital, Kathmandu University Teaching Hospital (KUTH). Materials and methods: A total no of 626 patients (male-299 and female-327) attending at outpatient clinic, in the department of Dentistry, Dhulikhel Hospital were taken in over a period of six months. The details about the permanent teeth to be extracted regarding each tooth type, including age and sex of the patient, type of tooth extracted, cause of extraction were collected, causes other than dental caries and periodontal disease were excluded. Results: The highest proportion of extraction due to caries occurred between 21-30 years of age, while that of periodontal disease was between 51-60 years of age. More than 80% of teeth lost were from below 40 years of age group. Mandibular first molar was by far the most frequently extracted tooth due to dental caries followed by maxillary first molar. Maxillary teeth were lost more than mandibular teeth due to periodontal disease. Conclusion: Dental caries and periodontal disease are the two most important factors for extraction or removal of tooth. In this study dental caries is the major cause for loosing tooth among young group of people. Key words: dental caries, periodontal disease, extraction doi: 10.3126/kumj.v7i1.1767 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 59-62